Polyaniline-fly ash nanocomposites synthesized via emulsion polymerization: Physicochemical, thermal and dielectric properties - Ramanath Prabhu (KeAi Communications Co., Ltd., 2021)
The polyaniline (PANI)/nano-fly ash composites were synthesized by Inverted emulsion polymerization technique. The FTIR spectrum of PANI/nano-fly ash composite (50/50) shows the vibrational bands due to N–H stretching (2165 cm−1), quinoid (1517 cm−1) and benzenoid ring stretching (1354 cm−1), etc. The UV–Visible absorption shows an absorption peak at 267 and 374 nm for PANI/nano-fly ash composite. Raman spectrum of composite shows peaks at 1635, 1339, 1179, 829, 569, 414 and 200 cm−1. The conductivity of pure polyaniline was decreased as a result of the addition of nano fly ash. X-ray diffraction of the composite shows two crystalline peaks at 20.9° and 26.2° (2Θ). The stability of pure PANI is enhanced by the incorporation of nano -fly ash. The coating of polyaniline on nano-fly ash has been confirmed by FESEM pictures. The AC conductivity was explained using the hopping model. The dielectric constant decreases as the frequency increases, it was explained by using Maxwell–Wagner polarization theory.